Writing for developers - Sarna, Piotr; Dunlop, Cynthia (Manning Publications, 2025)
Pragmatic methods for writing blogs, articles, and other technical pieces that stand out from the crowd! Do you want to connect with your community, share your state-of-the-art achievements, and help your peers benefit from your hard-fought lessons learned? Do you want to get the kind of attention that expands your career? Master the art of writing engineering blog posts and articles! This comprehensive guide shows you how to create content your fellow developers will love to read and share. Writing for Developers is full of the practical tips, tricks, and techniques you need to translate the ideas floating around your head into content that's clear and compelling, including how to: Pinpoint topics that make intriguing posts Apply popular blog post design patterns Rapidly plan, draft, and optimize blog posts Make your content clearer and more convincing to technical readers Tap AI for revision while avoiding misuses and abuses Increase the impact of all your technical communications Whether you're brand new to writing, or a seasoned hand who wants more attention for your work, Writing for Developers will help ensure your writing resonates with readers. This isn't a generic writing guide--from start to finish, the book is laser-focused on technical topics, writers, and audiences. Authors Piotr Sarna and Cynthia Dunlop combine their differing perspectives as an engineer and professional writer to help you write compelling works. You'll learn through detailed examples, methodical strategies, and a "punk rock DIY attitude!" About the Technology A well-crafted technical article can spark a new idea, demystify a technology, expand your perspective, or save you from going down a disastrous path. Even if you don't consider yourself a "good writer," you can make a difference by sharing insights and advancing the community. This practical guide shows you how to create blogs, articles, and other content your fellow developers will want to read and share. About the Book Writing for Developers introduces seven popular patterns for modern engineering blogs--such as "The Bug Hunt," "We Rewrote It in X," and "How We Built It"--and helps you match these patterns with your ideas. This book covers the entire writing process, from brainstorming, planning, and revising, to promoting your blog in ways that build reputation and generate further opportunities. What's Inside Rapidly plan, draft, and review your content Build on popular blog post design patterns Support your writing with AI Increase the impact of all your communications About the Reader For developers and engineers of all ability levels--even if you're not a native English speaker and never took a writing class in your life. About the Authors Piotr Sarna is a software engineer and an experienced book and blog author. Cynthia Dunlop has been writing for and with developers for 20+ years. Quotes Loaded with specific examples of writing in the wild that can serve as object lessons. - From the Foreword by Bryan Cantrill Demystifies the technical writing process and helps make you a better writer. - Alex Gallego, Redpanda Full of simple, practical guidance for improving your craft and increasing your impact. I will be recommending it far and wide. - Charity Majors, Honeycomb Offers lots of actionable tips, even for those who have been writing for years. Plus, it's a seriously fun read. - Glauber Costa, Turso.
Online resource; title from title details screen (O'Reilly, viewed March 17, 2025)
Keywords: Technical writing; Blog authorship; Communication of technical information; Software engineering; Rédaction technique; Information technique; Génie logiciel; technical writing; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet